Severe Malaria: Metabolic Complications - Planche, T.; Krishna, S. (Current Molecular Medicine, 2006)
Metabolic complications of severe malaria are some of the most important and potentially treatable manifestations of this deadly disease. The commonest metabolic complications (lactic acidosis and hypoglycaemia) arise from increased host anaerobic metabolism probably due to a mismatch between tissue oxygen supply and requirement. Optimising treatments for these complications should be guided by detailed understanding of their underlying pathophysiology, and may help to reduce the intolerably high case fatality rate of severe malaria.
Keywords: acidosis